2014
DOI: 10.1155/2014/293603
|View full text |Cite
|
Sign up to set email alerts
|

Aerodigestive Foreign Bodies in Adult Ethiopian Patients: A Prospective Study at Tikur Anbessa Hospital, Ethiopia

Abstract: Introduction. Foreign bodies (FBs) in the aerodigestive tract are important causes of morbidity and mortality and pose diagnostic and therapeutic challenges. The best method of removal of an esophageal and tracheobronchial FB is endoscopic guided extraction. Objective. To present our experience of the removal of aerodigestive FBs in adult Ethiopian patients using rigid endoscopes. Methods. A hospital-based prospective study, at Tikur Anbessa Referral and Teaching Hospital, from January 2011 to December 2012 (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…They were the most common type of foreign body in all age groups, and fish bones were most commonly located in the tonsils (48.5%) (Table ). This high rate of fish bone ingestion is in agreement with several previous studies reporting variable rates of fish bone ingestion of up to 90.4%, although some studies identified other types of foreign bodies as the most frequent, including a study of coin ingestion by children . The types of foreign bodies ingested were influenced by differences in the characteristics of the study groups, such as age and dietary habits.…”
Section: Discussionsupporting
confidence: 91%
“…They were the most common type of foreign body in all age groups, and fish bones were most commonly located in the tonsils (48.5%) (Table ). This high rate of fish bone ingestion is in agreement with several previous studies reporting variable rates of fish bone ingestion of up to 90.4%, although some studies identified other types of foreign bodies as the most frequent, including a study of coin ingestion by children . The types of foreign bodies ingested were influenced by differences in the characteristics of the study groups, such as age and dietary habits.…”
Section: Discussionsupporting
confidence: 91%
“…[5] Bronchoscopy is the treatment modality of choice and surgery is rarely required. [4] Pearl head pins behave as floating objects, mobile in nature especially in the early phase of inhalation and initial immediate preoperative X-rays are beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Rigid esophagoscopy requires general anesthesia and is associated with its own complications, but experience and outcome of its use are generally encouraging. [5]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have also been studies on ways of improving the management outcomes [8][9][10][11]. In the present study, we studied prospectively the pattern of presentation of patients in a single institution with FB inaerodigestive tract and incidence of intra-operative complications following rigid esophagoscopy/ bronchoscopy and the incidence of successful outcome after this procedure.…”
Section: Introductionmentioning
confidence: 99%